Photodynamic therapy in the treatment of trophic venous ulcers - Nasyrov M. V., Lukyianchikov V. N. (Interactive science, 2016)
this article describes the analysis of results of treatment of 126 patients with trophic ulcers of the lower extremity venous etiology. Photodynamic therapy was used in the I group patients (n = 77). The standard treatment was performed in the II group (n = 49). The authors showed that the use of photodynamic therapy helped to reduce preoperative period 3 times and to make autodermaplasty of trophic ulcers in the I group on 5,2 ± 0,4 days. Full autodermotransplantata engraftment was observed in the I group in 75,4% of patients and in the II group – 46,8%. Photodynamic therapy has a strong antibacterial effect and improves the processes of epithelialization.
Keywords: фотодинамическая терапия; венозная трофическая язва; хроническая венозная недостаточность; photodynamic therapy; venous trophic ulcers; chronic venous insufficiency